2016
DOI: 10.1113/ep085583
|View full text |Cite
|
Sign up to set email alerts
|

A1‐Adenosine receptor activation has biphasic roles in development of acute kidney injury at 4 and 24 h of reperfusion following ischaemia in rats

Abstract: New Findings r What is the central question of this study?A 1 -Adenosine receptor (A 1 AR) blockade before renal ischaemia aggravated kidney injury after 24 h reperfusion in several studies, whereas we previously observed a renoprotective effect of A 1 AR blockade during a 4 h reperfusion period. What are the underlying mechanisms for this biphasic effect of pretreatment with an A 1 AR antagonist at 4 and 24 h reperfusion?r What is main finding and its importance?A 1 -Adenosine receptor blockade protects the k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 41 publications
1
19
2
Order By: Relevance
“…The renal I/R-induced urine concentrating inability is mainly due to disturbed countercurrent multiplication mechanism by severely damaged TAL and disestablishment of medullary interstitial hyperosmolality Moosavi et al, 2009;Najafi et al 2016), as observed by the indirect index of low urine osmolality in all ischaemic groups in the present study. The fall of U osm by 40%…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…The renal I/R-induced urine concentrating inability is mainly due to disturbed countercurrent multiplication mechanism by severely damaged TAL and disestablishment of medullary interstitial hyperosmolality Moosavi et al, 2009;Najafi et al 2016), as observed by the indirect index of low urine osmolality in all ischaemic groups in the present study. The fall of U osm by 40%…”
Section: Discussionsupporting
confidence: 61%
“…It is important to mention that all renal parameters were assessed at 24 h reperfusion in the studies of Park et al and Li et al Recently, we found two different patterns of lymphocyte migration into the kidney following 30 min bilateral renal arterial clamping (Najafi, Owji, Kamali-Sarvestani, & Moosavi, 2016). Lymphocytes mostly aggregated in the cortical periarterial spaces up to 4 h of reperfusion, but then gradually infiltrated the interstitium during 24 h of reperfusion to contribute to intensifying renal injury.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations